Triphora lutea Suter 1908 - Bakker, Piet A. J.; Albano, Paolo G. (Zenodo, 2022)
Triphora lutea Suter, 1908 Triphora lutea Suter, 1908: 39, pl. 3, fig. 50. Cautor lutea (Suter, 1908) — Finlay 1926: 384, 386. Type locality. New Zealand, near the Snares Islands. Type material. Type material not located so far. Distribution. New Zealand (Suter 1908; Suter 1913; Odhner 1924; Finlay 1926; Powell 1979). Published as part of Bakker, Piet A. J. & Albano, Paolo G., 2022, Nomenclator, geographic and stratigraphic distribution of the family Triphoridae (Mollusca: Gastropoda), pp. 1-216 in Zootaxa 5088 (1) on page 107, DOI:10.11646/zootaxa.5088.1.1, http://zenodo.org/record/5836536